Pengalaman Single Parents dalam Merawat Anak yang Terkonfirmasi Positif Covid-19 - Padila Padila; Juli Andri; Andry Sartika; Muhammad Bagus Andrianto; Harsismanto J (Jurnal Kesmas Asclepius, 2021)
This study aims to explore the experience of single parents in caring for children with confirmed COVID-19. This research design is qualitative research with a phenomenological approach. The results of this study obtained six themes, namely the signs of COVID-19 symptoms that occur in children, namely children have fever, cough, runny nose, and loss of appetite, the transmission of covid-19 occurs due to lack of implementing health protocols and traveling to crowded places, when knowing their child confirmed that covid-19 single parents experience feelings of anxiety, panic and worry, single parents, get support from family, the surrounding environment and work friends. In conclusion, in caring for their children, single parents prepare children's needs such as medicines, vitamins, healthy food, and a comfortable play environment. In dividing the time to care for children confirmed positive for COVID-19, on average, mothers ask for leave at home. Keywords: Covid-19, Phenomenology, Caring for Children, Single Parents